TINJAUAN TENTANG CLICKBAIT DI MEDIA - Olih Solihin; Rachmawati Widyaningrum; Farida Hariyati; Farida Hariyati; Zikri Fachrul Nurhadi; Effendi Agus Waluyo (Prodi Ilmu Komunikasi Universitas Putera Batam, 2022)
The ease of access to information via the internet certainly has a positive impact on the community, and at the same time the community also accepts the negative impact. One negative thing is the growth of clickbait produced by online mass media. This paper aims to examine clickbait starting from the definition, types of clickbait, the advantages and disadvantages of using clickbait in terms of business and journalism. This study uses a qualitative approach, using content analysis as the main research data source. The author reviews various journals that examine clickbait, books, and website searches. The results show that the use of clickbait is a strategy by the mass media to persuade their readers to visit their website, then the number of reader visits is used as the basis for media companies to compete with their business partners. Clickbait provides business benefits in a limited time, while from a journalistic perspective it is clearly very detrimental, because the journalistic quality is very bad.